Pengembangan Uji Instrumen Tiga Tingkat dengan CRI untuk Mendeteksi Miskonsepsi dalam Pembelajaran Reaksi Redoks - Fatayatul Hasniyah; Zainuddin Muchtar (Universitas Negeri Medan, 2021)
Research has been carried out to develop a Three Tier Instrument Test with Certainty of Response Index (CRI) with the aims to find out (1) analysis of teaching learning chemistry, (2) the eligibility categories in terms of expert validation, (3) the percentage of misconceptions in each sub-concepts of redox reaction, and (4) the causes of students’ misconceptions about redox reaction material. The instrument is prepared with 10 items validated contains each sub concepts. Research results show that: (1) teaching learning chemistry using curriculum 2013, various student textbooks and methods so research develop many aspects of question instruments that needed in research by interviewing the teacher of each schools, (2) the test instrument has very decent criteria with the assessment of material, language, and construction aspect, (3) the lowest percentages of students’ misconception in redox reaction’s sub-concept is oxidizing and reducing agent in reaction (54.09%) and the highest percentages is in sub-concept of autoredox concept (69.98%) with all categories of misconceptions are enough, (4) the causes of students’ misconceptions in learning redox reaction found in the material, learning source, teachers aspect. It because students were taught by different teacher, different method, and different source in learning redox reaction.